1972
DOI: 10.1210/jcem-34-4-736
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Estrogens and Catechol Amines III. Studies on the Methylation of Catechol Estrogens, Catechol Amines and other Catechols by the Catechol-O-Methyltransferase1 of Human Liver

Abstract: The substrate specificity of the catechol-O-methyltransferase, purified from human liver 380-fold, has been tested with a variety of compounds. Cateehol estrogens, as well as cateehol amines are methylated to their corresponding monomethyl ethers. The relation of the rates of methylation of cateehol estrogens and cateehol amines depended on enzyme and substrate concentration; under standard assay conditions, 2-hydroxy-17P-estradiol was the preferred substrate for the enzyme, as compared with epinephrine and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(72 citation statements)
references
References 16 publications
2
69
0
1
Order By: Relevance
“…The ratio of aromatase to estrogen 2-hydroxylase activity in PIH placentas was also higher than that in normal placentas. It has been reported that the 2-hydroxyestrogens can modify the action of catecholamines by inhibiting COMT and a relationship between catechol estrogen metabolism and PIH [9][10][11] has been suggested. Gelbke et al [6] showed that the administration of 20 mg of estrone increased systolic and diastolic blood pressure 1 h after the injection at which time the maximal increase in 2-methoxyestrone levels in serum was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of aromatase to estrogen 2-hydroxylase activity in PIH placentas was also higher than that in normal placentas. It has been reported that the 2-hydroxyestrogens can modify the action of catecholamines by inhibiting COMT and a relationship between catechol estrogen metabolism and PIH [9][10][11] has been suggested. Gelbke et al [6] showed that the administration of 20 mg of estrone increased systolic and diastolic blood pressure 1 h after the injection at which time the maximal increase in 2-methoxyestrone levels in serum was observed.…”
Section: Discussionmentioning
confidence: 99%
“…They also confirmed that both activities were exhibited in Chinese hamster ovarian cells transfected with human placental aromatase cDNA, pH /3-Aro. On the other hand, it has been suggested that the effect of catechol estrogens on human placental steroidogenesis may be related to pregnancy-induced hypertension (PIH) because of evidence indicating that the catechol estrogens can modify the action of catecholamines by inhibiting of catechol-0-methyltransf erase (COMT) as competitive inhibitors [9][10][11]. However, the metabolism and physiological significance of catechol estrogens have not yet been determined completely.…”
mentioning
confidence: 99%
“…Increased 16 -hydroxylation in women is associated with increased breast cancer risk (Muti et al 2000). 16 -Hydroxylated metabolites stimulate breast cancer cell growth, whereas the 2-hydroxylated estrogens inhibit cell growth (Ball et al 1972, Seegers et al 1989, Lottering et al 1992, Zhu & Conney 1998. 2-OHE 1 and 2-OHE 2 are rapidly converted to the monomethyl ethers, 2-ME 1 and 2-ME 2 respectively by the enzyme catechol-O-methyltransferase (COMT) (Ball et al 1972, Jefcoate et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…16 -Hydroxylated metabolites stimulate breast cancer cell growth, whereas the 2-hydroxylated estrogens inhibit cell growth (Ball et al 1972, Seegers et al 1989, Lottering et al 1992, Zhu & Conney 1998. 2-OHE 1 and 2-OHE 2 are rapidly converted to the monomethyl ethers, 2-ME 1 and 2-ME 2 respectively by the enzyme catechol-O-methyltransferase (COMT) (Ball et al 1972, Jefcoate et al 2000. 2-ME 2 inhibits the growth of human mammary cancer cells in vitro and in vivo (Lottering et al 1992, Fotis et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…COMT has a role in the biosynthesis of melanin (Pavel, 1993) and several investigators have postulated the involvement of this enzyme in such human mental disorders as depression and schizophrenia (Murphy and Wyatt, 1975). COMT also inactivates L-Dopa, a catechol-containing drug used as a dopamine precursor in the treatment of Parkinson's disease (Ball et al, 1972;Guldberg and Marsden, 1975). Due to its harmful effect on the medication of Parkinson's disease, a great deal of interest has been directed towards the development of specific COMT inhibitors (Guldberg and Marsden, 1975 ;Mannisto and Kaakkola, 1989) and the determination of the structure of the enzyme itself.…”
mentioning
confidence: 99%